Peningkatan Manajemen Perpustakaan dengan Sistem Otomasi (Upaya Pelayanan Terhadap Pengguna Perpustakaan) - M Hadi Purnomo (STAIFAS-Press, 2016)
Improved library services is a very important impact on the need for improvement of library services with the automation system in order to produce the maximum level of service. Human resources (HR Librarian) owned by the library should be the ones who have the educational background of library science with a number of librarians tailored to the needs of the library, as this will greatly affect the system of work in progress. The existence of these librarians will be very supportive tercip-Nyanya useful libraries and support the advancement of education and the achievement of national education goals.Key Word: Library Management, system automation.